Hybrid Video Compression using 2D-DCT and Area Encoding Techniques - Thavamani, U.; Mahesh, Dr.K. (IJRDO -Journal of Computer Science Engineering, 2016)
To store the digital video, even CD/DVD is not sufficient of handling data and therefore, video compression plays an essential role. Video compression removes the redundant information from digital video without reduce the quality to an unacceptable level. In this proposed work, compressing video is efficiently done by using 2D-DCT which is a version of DCT with Median filter and Area encoding gives the high CR than existing algorithms. In this method, first video is divided into frames and remove noises using of Median Filter, then that frames are split in to 8x8 pixel blocks. Then 2D-DCT is employed on these blocks and after that, quantization, zigzag pattern and Area encoding is done on transformed data. Quality of video is good after compressed the video and also algorithm is fast with less complexity. Experimental results of the proposed work ensure that effectiveness and gives highest compression ratio without data loss and quality of video.